TOWARDS A GENERAL THEORY OF COLLABORATIVE PERFORMANCE: THE IMPORTANCE OF EFFICACY AND AGENCY. (24th August 2013) - DICKINSON, HELEN; SULLIVAN, HELEN
<x xml:space="preserve">Abstract</x> Much of what has been written about collaboration treats it instrumentally as a means–ends tool of improvement. However, despite considerable collaborative activity there is little evidence that clearly links collaboration to improvements in service‐user outcomes or reduced inequalities. In this article we draw on literature from critical public policy and governance studies to recast collaboration as an expression of cultural performance associated with a rather different set of values and measures. We argue that understanding collaboration in the round means that we need to pay attention to all dimensions of performance including cultural performance. We argue that this in turn helps to explain the persistent appeal of collaboration amongst policy makers and practitioners.